A Survey in Analysing Increased Business Profitability by Instagram - JAIN, DR MANJULA (The journal of contemporary issues in business and government, 2021)
Digital marketing is a way of marketing followed by new generation marketers. In recent times traditional practices of marketing come-up to be less effective in terms of giving output. With the growth of technology more and more new age marketers are adapting digital marketing and Instagram is used as a platform for advertising products but a clear statistic idea related to efficiency of digital media marketing especially Instagram is not known. The current survey puts light on the effectiveness of digital media marketing – Instagram in advertisement of products and raised sales of articles. The survey carried shows that Social media platform – Instagram as a potential medium of conducting promotional activities and results in raised sales of a product. Thus, current study opens the future perspective to conduct more research on the connection of different social media platform and shopped articles.